Integrated transcriptomic and proteomic analysis reveals isolation and culture associated molecular changes in neonatal porcine pancreatic cell clusters - Chang-Yi Chen; Chen-Ling Chen; Chen-Wei Kao; Chen-Yi Chen; Wan-Wen Hung; Ching-Wen Chang; Jyuhn-Huarng Juang; Wan-Chun Li (Molecular Biology Reports, 2026)
Background While porcine Neonatal Pancreatic Cell Clusters (NPCCs) were potential alternative source of islets, their immaturity and heterogeneity make them inefficiently ameliorate hyperglycemia in rodents. Our previous work showed that NPCCs regress to a transitional-like state immediately after isolation and undergo dynamic transcriptional changes during short-term in vitro culture. The present study aimed to further delineate the molecular cues underlying these changes during porcine pancreatic tissue isolation and cultivation. Method Transcriptomic and proteomic analysis were performed to compare Neonatal Porcine Pancreata (NPP), freshly isolated NPCCs (NPCCs-0D) and 3-day in vitro cultured NPCCs (NPCCs-3D). Using an in-house analysis pipeline, molecular differences between groups were identified. Results NPCCs‑0D showed lower molecular abundance compared with NPP and NPCCs‑3D groups under the tested conditions. Gene Sets Enrichment Analysis (GSEA) revealed that pathways related to receptor signaling and cell–microenvironment interactions were enriched in NPP and NPCCs‑3D, highlighting the importance of external regulation in maintaining pancreatic tissue architecture. In contrast. organelle- and catalysis-associated gene sets were enriched in NPCCs‑0D, suggesting a transcriptionally active and adaptive state. Conclusion Collectively, these findings indicate that molecular differences among NPP, NPCCs-0D, and NPCCs-3D reflect changes in tissue organization, cellular composition, and adaptation to isolation and culture conditions, rather than a linear differentiation process.

Micro-macro evaluation of ISS-lime-fly ash stabilized saline soils under freeze-thaw cycling - Jiyun Nan; Dan Chang; Jiankun Liu; Yihui Yan; Xue Li; Jong-Sub Lee; Xusheng Wan; Liyang Wang (Bulletin of Engineering Geology and the Environment, 2026)

Identification and formation pathways of oxidation products of chlorinated paraffins during ozonation in municipal wastewater - Enrui Li; Hongping Wang; Yibin Sun; Song Tang; Chao Wang; Yi Wan; Xudong Jia; Hong Chang (Journal of Environmental Sciences, 2026)

Hierarchically structured superamphiphobic radiative cooling fabric for personal thermal management - Wen-Jing Zhao; Chao-Hua Xue; Xiao-Jing Guo; Jing-Jing Peng; Li Wan; Yan Yang; Shi-Hang Lv; Jin-Yu Wang; Teng-Xin Wang; Ming-Wei Chang (Chemical Engineering Journal, 2026)

Long-day photoperiod promotes growth of pea (Pisum sativum L.) via auxin biosynthesis and polar transport - Luping Gu; Tao Wan; Wenjie Chen; Guiyu Zhou; Huiyu Zhang; Chang Tan; Lars H. Wegner; Sergey Shabala; Xuewen Li; Jiayou Liu; Yingming Feng; Renfang Shen; et al. (Plant Science, 2026)

Interfacial and emulsifying properties of low-denatured soy protein prepared by self-coacervation - Shumin Zhang; Jiyang Cai; Zhuojia Lin; Chang Yang; Zhihong Lyu; Menghui Wang; Wentao Qian; Zhili Wan; Hongliang Li; Xiaoquan Yang (Food Hydrocolloids, 2026)

Enhanced Cuδ+ stability and active hydrogen supply at CuO/ZrO2 interface for efficient nitrate to ammonia conversion - Ning Liu; Wenrui Wan; Leylan Liu; Lei Yuan; Yuhan Wu; Mingming Sun; Bing Chang; Li Wang; Jing Fan; Jianji Wang (Chemical Engineering Journal, 2026)

Poricoic acid A administered during DSS exposure attenuates acute colitis in mice and is accompanied by barrier-associated changes and endpoint fecal microbiota shifts - Mei Wang; Kunkun Zhang; Danli Wang; Mingtao Cao; Rong Yong; Xiangqian Li; Wenyi Chen; Chengcheng Peng; Jiale Chang; Lu Fang; Feiyang Zhou; Yuyue Wan; et al. (Journal of Natural Medicines, 2026)

Yinhuapinggan granules regulate PI3K/AKT and RAS/MAPK pathways to inhibit Streptococcus Pneumoniae-induced inflammatory responses - Chujun Gu; Daojun Yu; Tianhang Chen; Aixin Chen; Chang Li; Huifen Zhou; Jiehong Yang; Haitong Wan (Archives of Microbiology, 2026)

Seasonal responses of land surface temperature to landscape patterns and multi-objective optimization in urban–rural fringe: a case study of Changqing District of Jinan City, China - Min Wang; Zihan Li; Xiaoyu Wang; Zhongjian Shen; Jinyan Wang; Huanan Wan; Chang’an Zuo; Tianran Wang (Environmental Monitoring and Assessment, 2026)

Primary amine-functionalized HTO/CMC/PVA composite films: Highly selective lithium adsorption and applications in complex lithium-containing systems - Shengkai Liu; Ruimeng Liu; Wenxuan Wang; Dandan Hu; Yu Han; Cong Li; Huiling Li; Chang Wan; Tai Peng; Wei Wang; Daxin Liang (Process Safety and Environmental Protection, 2026)

A mini review on micro/nanobubble-mediated interfacial enrichment and adsorption-coupled pollutant removal: Core mechanisms, application scenarios, and feasibility - Xianglin Chang; Fuxing Yan; Aofan Wang; Shouqiang Wan; Xiaoqiang Cui; Beibei Yan; Guanyi Chen; Ning Li (Chemical Engineering Journal, 2026)

Unveiling the dynamic evolution of ambient formaldehyde along transport pathways in the Pearl River Delta - Qinghua Chang; Daocheng Gong; Yiming Zhao; Ying Li; Zhuangxi Liu; Xinmei Guo; Tao Wan; Chengliang Zhang; Shuo Deng; Qinqin Li; Hao Wang; Boguang Wang (Atmospheric Environment, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Predictive design of UV-curable bio-based polyurethane acrylate adhesives: Integrating viscoelasticity, adhesion, and controlled degradation - Bowen Xu; Weiyi Wang; Honghu Li; Gaoteng Shi; Hong Jiang; Chang Su; Shaoyu Wang; Tong Wan; Biao Wang; Bowen Cheng (Chemical Engineering Journal, 2026)

Boron neutron capture therapy-driven secretory-autophagy sorting of immunogenic cargo into extracellular vesicles converts tumors into precision autologous vaccines - Xin Pan; Linwen Lv; Zhiliang Hu; Jiayi Wang; Haojun Liang; Jiaxin Wan; Junhui Zhang; Ruyu Yan; Juan Li; Ya-nan Chang; Xue Bai; Lu Zhang; et al. (Chemical Engineering Journal, 2026)

Shifting snake ranges in a warming world - Xinru Wan; Wei She; Wenke Chang; Guangping Huang; Huizhong Fan; Ziyan Liao; Guoliang Li; Xiaolong Hu; He Zhang; Zhenyu Wang; Weiwei Zhang; Fuwen Wei (Conservation Biology, 2026)
Climate change is driving major shifts in global snake biodiversity, yet large‐scale assessments across taxonomic, phylogenetic, and genetic dimensions remain limited, hindering effective conservation. We compiled 3,486,894 records of 3044 species across seven biogeographic realms to evaluate current spatial patterns of diversity and to project future range dynamics and conservation priorities under different climate change scenarios. We constructed species distribution models for 1201 species to project range dynamics under four shared socioeconomic pathways across 10 global climate models and then applied generalized linear mixed models that integrated genetic and phylogenetic diversity to assess conservation priorities. Of 1201 species, 542 (45.1%) were projected to experience significant range contractions (a mean range loss of 11.62%). Of these, 175 species (14.6%) were projected to undergo both range loss and shifts of more than 400 km, and 103 of 775 species (13.3%) were projected to exhibit range contraction and low genetic diversity. Range shifts were widespread, especially in the Palearctic, with >60% of genera expected to move >100 km. Species in tropical forests and montane habitats were disproportionately at risk of range contraction and range shifts. Current protected areas (PAs) covered only 20–40% of the ranges of threatened snakes, and 81 of 341 genera (23.7%), such as Boa and Lachesis , were projected to lose habitat more rapidly inside PAs than outside. We identified four groups of conservation priority based on range vulnerability, genetic risk, and conservation gaps: taxa facing both range contraction and long‐distance shifts; genetically vulnerable taxa with shrinking ranges; taxa inadequately covered by PAs; and taxa projected to lose habitat faster inside PAs than outside. These findings underscore the urgent need for spatially adaptive, genetically informed, and climate‐resilient conservation strategies to protect the evolutionary potential of global snake diversity.

Pressure-driven flavor formation in rapeseed oil: an integrated multi-omics approach - Yini Yang; Chang Zheng; Ran Zhao; Ya Xu; Lanhang Yao; Wenlin Li; Changsheng Liu; Chuyun Wan; Qi Zhou (Food Chemistry, 2026)

The influence of wood species on polyphenol profiles and sensory characteristics of spine grape (Vitis davidii Foex) brandy under two aging conditions - Bingbing Duan; Jiayi Li; Wei Chang; Mingyuan Zheng; Zhuowu Wan; Yujie Suo; Hasmik Merkeryan; Meilong Xu; Xu Liu (Food Research International, 2026)

A net-like colloid with peculiar CO2 sorption behavior formed by aggregation of organic ligand molecules in water - Jin Cai; Wan Chen; Hai Li; Xin Zheng; Han Tang; Ming-Ke Yang; Zi-Xuan Huang; Zi-Ying Zhao; Peng Xiao; Yun-Lei Peng; Xian-Ren Zhang; Long-Long Xie; et al. (Chemical Engineering Journal, 2026)

New evidence of private cast iron production during the Ming Dynasty at Xiaonongchang, Chongqing, China - Sun Tianqiang; Wang Hongling; Huang Wan; Li Dadi; Yan Chang; Xu Yuming; Li Yuniu (Archaeological and Anthropological Sciences, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Unveiling Mo doping effects in hydrated vanadium oxide cathodes for high-energy zinc-ion batteries: Evidence from operando synchrotron X-ray and DFT analysis - Sanna Gull; Hsu-Chen Cheng; En-Hao Li; Tsung-Yi Chen; Chung-Sheng Ni; Wan-Ju Yu; Hao-Hsiang Chang; Ai-Yin Wang; Ruey-An Doong; Chin-Lung Kuo; Yu-Chun Chuang; Bo-Hao Chen; et al. (Chemical Engineering Journal, 2026)

Vegetation restoration regulates slope-scale sediment source–sink transitions on the Loess Plateau: Evidence from field scouring experiments - Shixuan Zhou; Jingjing Li; Peng Li; Enhao Chang; Kunxia Yu; Xiaohuang Liu; Qian Wan; Yunqi Wang (Geomorphology, 2026)

Inhalation associated health risk assessment of atmospheric gaseous and size-resolved particulate PAHs in a large temperature range of 50 °C - De-Qi Wang; Shi-Ming Jia; Li-Yan Liu; Chang-Yu Weng; Wan-Li Ma (Atmospheric Pollution Research, 2026)

Unraveling the impact of microplastics on autoimmune diseases: hidden dangers and environmental triggers - Yu-Tong Tan; Wei-Wei Wang; Shu-Zhen Xu; Yu-Wan Chang; Lei Li; Peng Wang; Hai-Feng Pan (Environmental Geochemistry and Health, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Synergistic effects and mechanism of recombinant viral vector-mediated STAT1 overexpression and STAT3 silencing on glioma U251 apoptosis - Xin-Long Hu; Hong Li; Guo-Dong Zhang; Chao Lin; Ping Huang; Xiu-Feng Chen; Fang Wan; Chang-Wu Dou; Hai-Tao Ju (Molecular Biology Reports, 2025)

Mechanistic Insights into Flood Pulse-Induced Ecological Benefits and a Balanced Eco-Risk Assessment Framework - Yujie Cai; Yuqing Chang; Xinhua Zhang; Li Wan; Zhurui Gao; Jiannan Zhang; Yasmina TIR; Yijun Guo (Environmental Management, 2025)

Research on the Mechanism of Complex Water-flooded Layers and Well Logging Evaluation Methods in the M Oilfield - Wen-Yuan He; Ya-Dong Wu; Li-Xiang Feng; Chang-Xi Li; Jin-Bin Wan; Guo-Hui Ni (Applied Geophysics, 2025)

Hypoglycemic cucurbitane-type triterpenoids from fruits of Citrullus colocynthis - Hua-Wei Lv; Yu Wan; Wen-Lin Fan; Meng-Di Zhu; Qiao-Liang Wang; Zhong-Bo Zhou; Chang-Chun Chen; Hong Wang; Xing-Nuo Li (Phytochemistry, 2025)

Design of BNT-based ceramics with enhanced energy density and ultrahigh polarization under moderate electric field via introducing BMW - Pan Gao; Wenjing Geng; Chang Liu; Hanjun Wang; Yun Ling; Yubo Li; Hongyan Wan; Haijuan Li; Xincheng Ren (Chemical Engineering Journal, 2025)

Pollution characteristic and temporal trend of PM2.5-bound heavy metals in a megacity of Northeast China: Implication for the effect of air pollution control policy - Jin-Wen He; Li-Yan Liu; Chang-Yu Weng; De-Qi Wang; Shi-Ming Jia; Wan-Li Ma (Atmospheric Pollution Research, 2025)

Fusaritricins E–G, three new polyketides, isolated from the endophytic fungus Fusarium sp. HC20 and their antifungal activities - Xu-Ri Wan; Chang Li; Ling-Yan Liu; Fang Yue; Xuan Lu; Yue-Hu Pei; Yi-Hui Yang (Phytochemistry Letters, 2025)

Size distribution and gas/particle partitioning of organophosphorus flame retardants in indoor and outdoor air of garment factories - Yi-Fan Zhang; Li Song; Wan-Li Ma; Chang-Yu Weng; Shi-Ming Jia; Yu Sun; Li-Yan Liu (Environmental Research, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Unravelling the mechanisms underlying marine redox shifts during sedimentary manganese metallogenesis: insights from the Carboniferous Muhu deposit, China - Zhi-Guo Dong; Bang-Lu Zhang; Lian-Chang Zhang; Fei-Yu Dong; Jie Li; Zi-Dong Peng; Bo Wan; Chang-Le Wang (Mineralium Deposita, 2025)

ChpR-displaying bacteria for bioremediation of chlorpyrifos and TCP: A whole-cell biosorbent approach - Yan Guo; Can Wu; Shun-yu Hu; Yu-xuan Xie; Wan-yan Wu; Bo-xin Li; Yu-ting Chen; Chang-ye Hui (Water Research, 2025)

Comparative assessment of thyroid disrupting effects of ethiprole and its metabolites: In silico, in vitro, and in vivo study - Zheyuan Song; Zheng Ma; Xueshan Feng; Rui Huang; Qiong An; Yunrui Pan; Jing Chang; Bin Wan; Huili Wang; Jianzhong Li (Journal of Environmental Sciences, 2025)

Animal farming and the oral microbiome in the Agricultural Health Study - Vicky C. Chang; Vaishnavi Purandare; Shilan Li; Gabriella Andreotti; Xing Hua; Yunhu Wan; Casey L. Dagnall; Kristine Jones; Belynda D. Hicks; Amy Hutchinson; Yukiko Yano; Kathryn R. Dalton; et al. (Environmental Research, 2025)

Inhibition of detoxification enzyme gene expression by MON@PDA nano-adjuvant to overcome insecticide resistance - Qinghong Zeng; Tianqing Gao; Hu Guo; Dongjian He; Dan Sun; Chang Yu; Fangge Shang; Gang Wu; Jianhong Li; Shun He; Hu Wan (Chemical Engineering Journal, 2025)

Nanoparticles co-delivering double-stranded RNA and insecticide enhance control efficacy and overcome pest resistance - Chao Hu; Chang Yu; Jiaqing Li; Yuxi Liu; Qinghong Zeng; Hu Wan; Shun He; Yuting Li; Ping Gao; Yuntong Lv; Kunyan Zhu; Subba Reddy Palli; et al. (Chemical Engineering Journal, 2025)

Natural deep eutectic solvent-ultrasonic-enzyme combination assisted extraction: Establishment of an integrated method and application on Astragalus polysaccharides - Lulu Ye; Haofang Wan; Yihang Lu; Jiehong Yang; Yu He; Haitong Wan; Chang Li (Sustainable Chemistry and Pharmacy, 2025)

An interpretable and scalable model for rapid flood extent forecasting using satellite imagery and machine learning with rotated EOF analysis - Hung-Hsien Wan; Hyongki Lee; Tien Le Thuy Du; Amirhossein Rostami; Chi-Hung Chang; Kel N. Markert; E. James Nelson; Gustavious P. Williams; Sanmei Li; William Straka; Sean R. Helfrich; Franz J. Meyer (Environmental Modelling & Software, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

New insights into rhizosphere bacterial community shaped by lettuce genotypes for divergent degradation efficiencies of phthalates - Guang-Xuan Tang; Yu-Hong Huang; Li-Wan Feng; Yu-Chang Hu; Jia-Lu Wei; Huixiong Lü; Li-Hui Liu; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; et al. (Journal of Hazardous Materials, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

MOF-derived transition metal phosphides for rechargeable batteries - Pengbiao Geng; Bing Ji; Yuyang Guo; Cunchong Xiao; Jiasheng Wan; Chang Ming Li (Chemical Engineering Journal, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Fabrication of sesamin-loaded sodium caseinate nanoparticles: Insight to characterization, in vitro digestion, and molecular docking analysis - Wan-Yi Liu; Tzu-Yu Chen; Yun-Shan Hsieh; Yung-Yi Cheng; Shiou-Ling Li; Li-Ching Chang; Yu-Tse Wu (Food Bioscience, 2025)

Gradient-Structured sodiophilic skeleton integrated with spatial confinement effect Enables high-rate and ultra-stable Na metal batteries - Fang-Yu Tao; Dan Xie; Wan-Yue Diao; Chang Liu; Godefroid Gahungu; Wen-Liang Li; Jing-Ping Zhang (Chemical Engineering Journal, 2025)

In situ global mapping of protein perturbations via protein abundance and conformation analysis - Yi Li; Xingchao Yang; Fei Zheng; Hanqing Zhang; Chang Shao; Ning Wan; Haiping Hao; Hui Ye (Analytica Chimica Acta, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Membrane distillation localized heating in high-salinity wastewater treatment: Mechanisms, performance and challenges - Yuxuan Wan; Huarong Yu; Ruixiang Li; Haiqing Chang; Dan Qu; Fangshu Qu (Resources, Conservation and Recycling, 2025)

Curcumin protects rat endplate chondrocytes against IL-1β-induced apoptosis via Bcl-2/Bax regulation - Chao Wan; Shixing Liu; Long Zhao; Chengbing Chang; Hewen Li; Rui Li; Bin Chen (Journal of Molecular Histology, 2025)

Genomic, transcriptomic, and metabolomic analyses reveal convergent evolution of oxime biosynthesis in Darwin’s orchid - Kai Jiang; Birger Lindberg Møller; Shaofan Luo; Yu Yang; David R. Nelson; Elizabeth Heather Jakobsen Neilson; Joachim Møller Christensen; Kai Hua; Chao Hu; Xinhua Zeng; Mohammed Saddik Motawie; Tao Wan; et al. (Molecular Plant, 2025)

Protection of glutamine: The NF-κB/MLCK/MLC2 signaling pathway mediated by tight junction affects oxidative stress, inflammation and apoptosis in snakehead (Channa argus) - Xue-qin Wu; Ji-wu Wan; Zhi-nan Yang; Hong-jian Liu; Yue Chang; Si-bo Peng; Xiao-tian Niu; Yi-di Kong; Min Li; Xiu-mei Chen; Gui-qin Wang (Fish & Shellfish Immunology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Innovative supramolecular coordination nanomedicine: Targeting inflammation and scavenging ROS for synergistic arthritis therapy - Xuzhuo Chen; Tianhao Wan; Mengxue Shi; Chang Li; Zhenqiang Wang; Lingyan Cao; Fengrong Dai; Weifeng Xu; Shanyong Zhang (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Antimicrobial perylenequinones isolated from the endophytic fungus Alternaria alstroemeriae - Yong-Fu Li; Fang Yue; Xu-Ri Wan; Chang Li; Yi Sun; Yue-Hu Pei (Phytochemistry Letters, 2025)

Study on the kinetics and reaction mechanism of low-temperature oxidation of lignite with different coalification - Jianqiao Zhao; Zheng Wei; Chang Shi; En Meng; Bingchen Gu; Ning Li; Shi Yu; Xianliang Meng; Ruizhi Chu; Guoguang Wu; Xiaofeng Jiang; Xiao Li; et al. (Fuel, 2025)

Mechanistic insight into the neurodevelopmental toxicity of the novel pesticide pyrifluquinazon (PFQ) and its major metabolite in early-life stage zebrafish - Rui Huang; Zijun Liu; Yunrui Pan; Zheng Ma; Huili Wang; Bin Wan; Jianzhong Li; Jing Chang (Environmental Pollution, 2025)

Associations Between Organophosphate Esters Exposure and Metabolic Syndrome: Exploring the Mediating Role of Oxidative Stress and Inflammation in Adults - Sijie Yang; Yaping Li; Ling Liu; Zhengce Wan; Qitong Xu; Chang Xie; Lulu Song; Youjie Wang; Hui Chen; Surong Mei (Exposure and Health, 2025)

Tree biology: From genomics to genetic improvement - Jinbo Shen; Wan-Feng Li; Chang Liu; Shuai Zheng (Plant Science, 2025)

Progress in Transdifferentiation of Autologous Alternative Cell Sources into Corneal Epithelial Cells - Bei Wang; Jiang-Lan Zhao; Wan-Ying Cai; Gong-Yue Wang; Yu-Zhi Li; Jia-Song Wang; Hua-Tao Xie; Ming-Chang Zhang (Stem Cell Reviews and Reports, 2025)

National investigation of bisphenols in the surface soil in China - Chang-Yu Weng; Ying-Ying Zhang; Fu-Jie Zhu; Shi-Ming Jia; Wan-Li Ma (Science of The Total Environment, 2024)

A comprehensive review of critical factors affecting green ammonia synthesis by electrochemical process - Cheng-Yi Li; Shen-Wei Chu; Chia-Yun Ho; Han-Jung Chang; Terng-Jou Wan (Journal of Environmental Chemical Engineering, 2024)

Clustering, triangulation, and evaluation of 3D lines in multiple images - Dong Wei; Haoyu Guo; Yi Wan; Yongjun Zhang; Chang Li; Guangshuai Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Hierarchically porous and flexible chitin-fiber/melamine-sponge composite filter with high-loading of PdAu nanoparticles for effective hydrodechlorination of chlorophenols - De-Chang Li; Zhengbin Tian; Xianliang Huang; Wan Zhang; Wenquan Wang; Qian Zhang; Xiaohui Deng; Guang-Hui Wang (Journal of Hazardous Materials, 2024)

The galactomannan-EGCG physical complex: Effect of branching degree and molecular weight on structural and physiological properties - Wan Wang; Junhui Chang; Zhihui Zhang; Haijing Liu; Li He; Yan Liu; Ji Kang; H. Douglas Goff; Zhenjing Li; Qingbin Guo (Carbohydrate Polymers, 2024)

Exploring the Potential of MIM-Manufactured Porous NiTi as a Vascular Drug Delivery Material - Yang Zhou; Tun Wang; Peng Lu; Zicheng Wan; Hao He; Junwei Wang; Dongyang Li; Yimin Li; Chang Shu (Annals of Biomedical Engineering, 2024)

Key aroma components in Lu'an guapian green tea with different aroma types from five tea tree varieties decoded by sensomics - Yuchuan Li; Jingtao Zhou; Wenluan Xu; Chang He; Junyu Zhu; De Zhang; Yuqiong Chen; Zhi Yu; Xiaochun Wan; Dejiang Ni (Food Bioscience, 2024)

Pollution characteristics and oxidative potential of atmospheric particles at a typical rural area: A case study during the Chinese Lunar New Year - Shi-Ming Jia; Chang-Yu Weng; Guo-Ying Wang; Wan-Li Ma (Atmospheric Pollution Research, 2024)

Deep Underground Earthquake Observation: Small to Moderate Earthquakes and Microearthquakes Identification - Chang Chen; Wentao Wan; Yun Wang; Jingsong Liu; Hongyi Li; Qiangqiang Miao; Yongsheng He; Juan Qi; Chao Wang (Journal of Earth Science, 2024)

Identification of ∼200 transformation products of polyhalogenated compounds to characterize their transformation pathways in sludges - Enrui Li; Tong Li; Xiao Yang; Shuzhan Zhang; Yi Wan; Hong Chang (Water Research, 2024)

Individual and joint effects of organophosphate esters and hypertension or diabetes on renal injury among Chinese adults - Sijie Yang; Yaping Li; Mingye Zhang; Qitong Xu; Chang Xie; Zhengce Wan; Lulu Song; Yongman Lv; Youjie Wang; Hui Chen; Surong Mei (International Journal of Hygiene and Environmental Health, 2024)

A novel AP2/ERF transcription factor, NtERF10, positively regulates plant height in tobacco - Li Xu; Yong Xu; Jia-rui Jiang; Chang-xin Cheng; Wen-wu Yang; Le-le Deng; Qi-li Mi; Wan-li Zeng; Jing Li; Qian Gao; Hai-ying Xiang; Xue-mei Li (Transgenic Research, 2024)
Ethylene response factors have been shown to be involved in the effects of plant developmental processes and to regulate stress tolerance. The aim of this study was to recognize the regulatory mechanisms of ethylene response factors on tobacco plant height. In this study, a gene-edited mutant (ERF10-KO) and wild type (WT) were utilized as experimental materials. Transcriptome and metabolome analyses were used to investigate the regulatory mechanism of NtERF10 gene editing on plant height in tobacco. Here, through the analysis of differentially expressed genes (DEGs), 2051 genes were upregulated and 1965 genes were downregulated. We characterized the different ERF10-KO and WT plant heights and identified key genes for photosynthesis, the plant hormone signal transduction pathway and the terpene biosynthesis pathway. NtERF10 was found to affect the growth and development of tobacco by regulating the expression levels of the PSAA , PSBA , GLY17 and GGP3 genes. Amino acid metabolism was analyzed by combining analyses of differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs). In addition, we found that members of the bHLH, NAC, MYB, and WRKY transcription factor families have vital roles in regulating plant height. This study not only provides important insights into the positive regulation of the ethylene response factor NtERF10 on plant height during plant growth and development but also provides new research ideas for tobacco molecular breeding.

Association between organophosphate esters individual and mixed exposure with the risk of hyperlipidemia and serum lipid levels among adults in Wuhan, China - Qitong Xu; Chang Xie; Sijie Yang; Yaping Li; Mingye Zhang; Zhengce Wan; Lulu Song; Yongman Lv; Hui Chen; Youjie Wang; Surong Mei (Environmental Science and Pollution Research, 2024)

Associations of exposure to organochlorine pesticides and polychlorinated biphenyls with chronic kidney disease among adults: the modifying effects of lifestyle - Chang Xie; Sijie Yang; Yaping Li; Mingye Zhang; Qitong Xu; Zhengce Wan; Lulu Song; Yongman Lv; Dan Luo; Qiang Li; Youjie Wang; Hui Chen; et al. (Environmental Science and Pollution Research, 2024)

Absorption, distribution, metabolism, and elimination of epoxiconazole enantiomers in lizards (Eremias argus) - Qiong An; Weiyu Hao; Zheng Ma; Leisen Zhang; Zheyuan Song; Bin Wan; Peng Xu; Huili Wang; Jing Chang; Jianzhong Li (Chemosphere, 2024)

Spatial and temporal variation of water clarity in typical reservoirs in the Beijing-Tianjin-Hebei region observed by GF1-WFV satellite data - Chang Cao; Junsheng Li; Xiaodong Jia; Shenglei Wang; Bo Wan (Journal of Oceanology and Limnology, 2024)

Genomic and transcriptomic analysis reveals the genetic diversity and adaptive signatures of Maduo sheep - Li-Na Chang; Xue Gao; Shi-Xin Wu; Rui-Dong Wan; Zhan-Xing Yang; Hai-Mei Zhao; Ke Zhang; Xin-Quan Zhao; You-Gui Fang; Gong-Xue Jia (Small Ruminant Research, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Bridging the gap: Public engagement in blue-green space development for healthier urban futures - Yutong Zhao; Jia Li; Rebecca M. Collins; Kuntao Deng; Hongyu Wu; Linchuan Yang; Fei Chang; Jiangjun Wan (Journal of Environmental Management, 2024)

Concentration, composition and exposure risk assessment of particulate matter with different particle sizes in subway stations - Xinru Wang; Xin Meng; Li Chang; Fei Pei; Taocheng Wan; Tong Cui; Yiqiao Liu; Song Pan (Building and Environment, 2024)

Losing Tidal Flats at the Midpoint of the East Asian-Australasian Flyway over the past 100 Years - Wan-Jyun Chen; An-Yu Chang; Chia-Chi Lin; Ruey-Shing Lin; Da-Li Lin; Pei-Fen Lee (Wetlands, 2024)
The ecosystem services and functions of tidal flats have been overlooked for many decades, and tidal flat loss has been identified as a serious threat to many taxa in recent years, especially for migratory waterbirds. Despite the understanding of tidal flats change on the global scale, there are still a lot of unknowns on the small scale, including tidal flats in Taiwan, which are important stopover sites for migratory waterbirds along the East Asian–Australasian Flyway. Therefore, we collated historic topographic maps, Landsat Archive images between the 1920s and the 2020s to determine the trajectories of tidal flat change along the coastline of Taiwan. Our results show that tidal flat coverage expanded between the 1920s and the 1950s, but lost approximately 266 km 2 (58%) between the 1950s and the 2010s. The status of the tidal flats along the western coastline of Taiwan has been identified as “Endangered” based on the criteria of the IUCN Red List of Ecosystems. According to the aims of the Global Biodiversity Framework, we suggest rethinking the land use plans along the coastline to mitigate the tidal flat loss, especially the controversial issues concerning the expansion of green energy infrastructure. To realize the Nature Positive goals by 2030, recovering and restoring the tidal flat ecosystem could be one of the key strategies.

Patient-derived pathogenic microbe deposition enhances exposure risk in pediatric clinics - Wan Wang; Zongyao Qiu; Hui Li; Xiaorong Wu; Ying Cui; Lixiang Xie; Bozhen Chang; Peipei Li; Hong Zeng; Tao Ding (Science of The Total Environment, 2024)

Selective formation of high-valent iron in Fenton-like system for emerging contaminants degradation under near-neutral and high-salt conditions - Yue Yin; Jingjing Chang; Haisong Li; Xiaoyang Li; Junfeng Wan; Yan Wang; Weiming Zhang (Journal of Hazardous Materials, 2024)

Identification and oxidation of chlorinated paraffins containing nitrate esters, aliphatic sulfates, and thioether amino acids in sewage sludges - Enrui Li; Yibin Sun; Yi Wan; Song Tang; Chao Wang; Hong Chang (Water Research, 2024)

Mechanically stable superhydrophobic coating of crosslinked polymer composite with self-healing ability - Xiao-Jing Guo; Meng-Chen Huang; Chao-Hua Xue; Hui-Di Wang; Zhong-Xue Bai; Yong-Gang Wu; Chao-Qun Ma; Zhong-Yang Shao; Zi-Hao Jiang; Li Wan; A-Jun Chang; Jing Li; et al. (Chemical Engineering Journal, 2024)

Propeller hydrodynamic excitation influenced by shafting whirling vibration considering different nonuniform inflow conditions: A numerical study - Chang-Lin Meng; Lie-Yi Dong; Dong-Hua Wang; Jia-Xuan He; Zhi-Jun Shuai; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Ocean Engineering, 2023)

Overcoming resistance in insect pest with a nanoparticle-mediated dsRNA and insecticide co-delivery system - Haixiang Lv; Xuchao Li; Jiaqing Li; Chang Yu; Qinghong Zeng; Guogui Ning; Hu Wan; Jianhong Li; Kangsheng Ma; Shun He (Chemical Engineering Journal, 2023)

Insight into the effect of a heavy metal mixture on neurological damage in rats through combined serum metabolomic and brain proteomic analyses - Jie Xie; Fankun Zhou; Lu Ouyang; Qi Li; Shaoqi Rao; Rui Su; Shuo Yang; Jiajun Li; Xin Wan; Lingyu Yan; Peishan Liu; Hui Cheng; et al. (Science of The Total Environment, 2023)

An efficiency-driven approach for global ecological industrial parks - Shih-Fang Lo; Wen-Min Lu; Che-Wei Chang; Shiu-Wan Hung; Li-Ling Yang (Journal of Cleaner Production, 2023)

Research on stability and control strategies for a spring-loaded valve with bypass outlet - Jie Jian; Zhi-Jun Shuai; Jia-Xuan He; Chang-Lin Meng; Tao Yu; Xi Wang; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Annals of Nuclear Energy, 2023)

Pd sub-nanolayer on Au core for enhanced catalytic hydrogenation reduction of oxyanions pollutants: Synergistic effect of Pd and Au - Minghui Li; Hang Liu; Chang Liu; Yan Ding; Caixia Fang; Rui Wan; Hongjie Zhu; Yaning Yang (Environmental Pollution, 2023)

Association between multiple metal(loid)s exposure and renal function: a cross-sectional study from southeastern China - Guihua Du; Xiaoguang Song; Fankun Zhou; Lu Ouyang; Qi Li; Shiying Ruan; Shuo Yang; Shaoqi Rao; Xin Wan; Jie Xie; Chang Feng; Guangqin Fan (Environmental Science and Pollution Research, 2023)

Numerical investigation on the hydrodynamics of a hybrid OWC wave energy converter combining a floating buoy - Chang Wan; Can Yang; Xiaodong Bai; Chunwei Bi; Hailong Chen; Mingwei Li; Yeqing Jin; Lujun Zhao (Ocean Engineering, 2023)

ZmMS1/ZmLBD30-orchestrated transcriptional regulatory networks precisely control pollen exine development - Quancan Hou; Xueli An; Biao Ma; Suowei Wu; Xun Wei; Tingwei Yan; Yan Zhou; Taotao Zhu; Ke Xie; Danfeng Zhang; Ziwen Li; Lina Zhao; et al. (Molecular Plant, 2023)

Anti-substitution effect of coupling crop and livestock production on fertilizer use: Evidence from Chinese smallholder farms - Chang Li; Dongwei Wan; Xiangbo Xu; Jing Li; Paul P.J. Gaffney; Yuhao Ma; Linxiu Zhang (Journal of Cleaner Production, 2023)

Numerical study on unsteady propeller exciting characteristics considering shafting whirling vibration effect - Chang-Lin Meng; Zhi-Jun Shuai; Tao Yu; Ke-Xin Ren; Jie Jian; Xi Wang; Dong-Hua Wang; Wan-You Li; Chen-Xing Jiang (Ocean Engineering, 2023)

The impact of cautious coal power phase-out on decarbonization of China's iron and steel industry - Yifan Chang; Fang Wan; Jiarong Li; Na Liu; Xilong Yao (Journal of Cleaner Production, 2023)

Evolution of silicate weathering in South China since 30 Ma: Controlling factors and global implications - Hualong Jin; Shiming Wan; Chang Liu; Debo Zhao; Wenqiang Pei; Zhaojie Yu; Jin Zhang; Zehua Song; Mengjun Li; Yi Tang; Anchun Li (Global and Planetary Change, 2023)

A novel investigated method for decoupling adsorption and degradation effect on AFB1 based on isotope tracing and NMR analysis - Wan Zhang; Jun Wang; Jianpeng Dou; Tiantian Li; Hujun Liu; Xiaojiao Chang; Shengfeng Qian; Langao Lv; Wenfu Wu; Changpo Sun (Food Chemistry, 2023)

Greenhouse gas footprint assessment of wood-based panel production in China - Wan-Li Lao; Liang Chang (Journal of Cleaner Production, 2023)

Absence of water content contrast between lithosphere and asthenosphere in subduction zone - Yuto Sato; Eiichi Takahashi; Chang-Ming Xing; Li Li; Ze-Xian Cui; Wan-Feng Zhang; Xiao-Ping Xia (Earth and Planetary Science Letters, 2023)

Synthesis of Lanthanum-Modified Attapulgite and Its Phosphorus-Fixing Mechanism for Urban Eutrophic Lake - Lingfeng Ye; Ye Li; Cong Liu; Bolin Li; Dongxue Liu; Chang Liu; Jie Wan; Chengbin Fu (Water, Air, & Soil Pollution, 2022)

Distribution of ultrafine aerosols and volatile organic compounds from surgical smoke during electrocauterization - Chi-Tsung Chen; Shiang-Fu Huang; Cheng-Jung Li; Jou-Mien Huang; Kai-Ping Chang; Gwo-Hwa Wan (Air Quality, Atmosphere & Health, 2022)

The Effect of Co-Exposure to Glyphosate, Cadmium, and Arsenic on Chronic Kidney Disease - Junne-Ming Sung; Wei-Hsiang Chang; Kuan-Hung Liu; Chung Yu Chen; Trias Mahmudiono; Wan-Ru Wang; Ho-Chi Hsu; Zhen-Yi Li; Hsiu-Ling Chen (Exposure and Health, 2022)

The safety degree evaluation of marine biodiversity in China - Xiu-Mei Fu; Wan-Yu Wu; Fang Yang; Shan-Shan Jiang; Shi-Qi Wang; Xiao-Yan Li; Hui-Ying Tang; Ying Liu; Chang-Yun Wang (Journal of Coastal Conservation, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

The response of ABA and hydraulic indicator-mediated leaf gas exchange and nonstructural carbohydrate of Ginkgo biloba saplings to drought and rehydration - Zhicheng Chen; Chang Liu; Xin Li; Shan Li; Xianchong Wan; Shirong Liu (Acta Physiologiae Plantarum, 2022)

Establishment and characterization of the Bactrocera dorsalis (Diptera: Tephritidae) embryonic cell line QAU-Bd-E-2 - Gui-Ling Zheng; Jie Li; Qian-Long Yu; Bin Zhang; Xue-Meng Ding; Hui Li; Hong-Xu Zhou; Fang-Hao Wan; Chang-You Li (In Vitro Cellular & Developmental Biology - Animal, 2021)

miR-34c inhibits PDGF-BB-induced HAVSMCs phenotypic transformation and proliferation via PDGFR-β/SIRT1 pathway - Wei-feng Wan; Xin Zhang; Chang-ren Huang; Li-gang Chen; Xiao-bo Yang; Kun-yang Bao; Tang-ming Peng (Molecular Biology Reports, 2021)
The purpose of this study was to explore the effect of miR-34c on PDGF-BB-induced HAVSMCs phenotypic transformation and proliferation via PDGFR-β/SIRT1 pathway, so as to find a new method for early diagnosis and treatment of cardiovascular disease. HA-VSMCs were treated with platelet-derived growth factor-BB (PDGF-BB) at 0 h, 12 h, 24 h, 48 h or 36 h to explore the optimal time for phenotypic transformation of VSMCs. And then, PDGF-BB-induced HA-VSMCs were transfected with miR-34c mimics/mimics NC and pcDNA3.1-PDGFR-β/pcDNA3.1-NC to observe cell biological behaviour. CCK8 was used to detect cell proliferation activity. Transwell chamber assay was used to detect cell invasion. Early apoptosis was analyzed by flow cytometry. The expression of α-SMA and Smemb was detected by immunofluorescence staining. The expressions of PDGFR-β, IRF9, Acetyl-NF-κB/p65, Acetyl-p53 and CyclinD1 were analyzed by Western blot analysis. The expression of miR-34a, miR-34b and miR-34c was detected by RT-PCR, and the targeting relationship between miR-34c and PDGFR-β was detected by luciferase reporting assay. The results indicated the proliferation and migration of PDGF-BB-induced HA-VSMCs significantly increased, and apoptosis significantly decreased. Besides, α-SMA decreased significantly, while Smemb increased significantly. Furthermore, expressions of PDGFR-β, IRF9, Acetyl-NF-κB/p65, Acetyl-p53 and CyclinD1 increased significantly, and SIRT1 decreased significantly. Experimental results showed that, miR-34c mimics significantly inhibited cell proliferation and migration, and promoted cell apoptosis, and miR-34c inhibitor had the opposite effects. MiR-34c mimics significantly increased α-SMA expression and decreased Smemb expression, while the opposite effects were reflected after transfection with miR-34c inhibitor. Moreover, miR-34c mimics significantly decreased the expressions of PDGFR-β, IRF9, Acetyl-NF-κB/p65, Acetyl-p53 and CyclinD1, and significantly increased the expression of SIRT1, while miR-34c inhibitor had the opposite effects. Luciferase assay confirmed that PDGFR-β was a potential target of miR-34c. Subsequently, PDGF-BB-induced HA-VSMCs were co-transfected with miR-34c mimics and pcDNA3.1-PDGFR-β. The results indicated that PDGFR-β reversed the biological function of miR-34c mimic. The results revealed the potential application value of miR-34c as a marker molecule of phenotypic transformation, providing a potential target for improving phenotypic transformation.

Genesis of the Linghu Au deposit in Xiaoqinling Region, Henan province, China: Constraints from fluid inclusions and isotope systematics - Wei Zeng; Zhi-gao Wang; Duo Wan; Feng-yue Sun; Cheng-dong Li; Reng-an Yu; Jia-ying Wang; Jian-chang Xu (Arabian Journal of Geosciences, 2020)

Pharmacokinetics of seven major active components of Mahuang decoction in rat blood and brain by LC–MS/MS coupled to microdialysis sampling - Haoyu Wan; Lujia Pan; Yu Wang; Chang Li; Li Yu; Huifen Zhou; Haitong Wan; Yu He (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Identification of rs11615992 as a novel regulatory SNP for human P2RX7 by allele-specific expression - Tao Peng; Li Zhong; Jing Gao; Zhu Wan; Wei-Ping Fu; Chang Sun (Molecular Genetics and Genomics, 2020)

Environment‐ and trait‐mediated scaling of tree occupancy in forests worldwide - Haibao Ren; Petr Keil; Xiangcheng Mi; Keping Ma; Zhanqing Hao; Wanhui Ye; Luxiang Lin; Renato Valencia; Christine Dawn Fletcher; Duncan W. Thomas; Robert W. Howe; James Lutz; et al. (Global Ecology and Biogeography, 2019)
Aim The relationship between the proportion of sites occupied by a species and the area of a site [occupancy–area relationship (OAR)] offers key information for biodiversity management and has long fascinated ecologists. We quantified the variation in OAR for 3,157 woody species in 17 forest plots worldwide and tested the relative importance of environment and species traits for explaining this variation and evaluated overall model predictive ability. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We used mixed‐effect regression to examine the observed shape of the OAR (its “slope”) against species‐specific and plot‐wide predictors: coarse‐grain occupancy, tree size, plot species richness, energy availability and topographic complexity. Results We found large variation in OAR slopes, and the variation was strongest among species within plots. The OAR slopes showed a latitudinal trend and were steeper near the equator. As predicted, coarse‐grain occupancy and tree size negatively affected OAR slopes, whereas species richness had a positive effect and explained most of the variance between plots. Although hypothesized directionalities were broadly confirmed, traits and environment had relatively limited overall predictive power. Main conclusions These results document the variation of the OAR for 3,157 species at near‐global extent. We found a latitudinal gradient in OAR slopes and confirmed key hypothesized predictors. But at this global extent and over the large set of species analysed, the remaining unexplained variation in OAR slopes was substantial. Nevertheless, this large‐scale empirical analysis of the OAR offers an initial step towards a more general use of OARs for the fine‐scale prediction of species distributions and abundance.

The complete mitochondrial genome of the red-necked stint Calidris ruficollis (Charadriiformes, Scolopacidae) - Wan Chen; Wei Liu; Chenling Zhang; Kexin Li; Chaochao Hu; Qing Chang (Conservation Genetics Resources, 2019)

FcRγ deficiency improves survival in experimental sepsis by down-regulating TLR4 signaling pathway - Zhi-Min Wei; Zhuo Wang; Xiao-Jian Wan; Xian-Jing Li; Yi-Xing Li; Yang Bai; Xue Yang; Yong Yang; Shun-Chang Jiao; Zhe-Feng Liu (Immunologic Research, 2019)

An improved atmospheric correction method in repeat-pass InSAR measurements - Jie Zhu; Zhanqiang Chang; Xiaojuan Li; Jie Yu; Wen Yu; Yi Luo; Wei Wang; Xiangxing Wan; Shujun Qian (International Journal of Remote Sensing, 2018)

The mitochondrial genome of the Kentish Plover Charadrius alexandrinus (Charadriiformes: Charadriidae) and phylogenetic analysis of Charadrii - Wan Chen; Chenling Zhang; Tao Pan; Wei Liu; Kexin Li; Chaochao Hu; Qing Chang (Genes & Genomics, 2018)

Antioxidant and antihyperlipidemic activities of purified polysaccharides from Ulva pertusa - Weida Li; Kai Wang; Nanfang Jiang; Xiaolei Liu; Minghui Wan; Xintao Chang; Dongmei Liu; Huimin Qi; Shunmei Liu (Journal of Applied Phycology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

A cell clone strain from Mythimna separata (Lepidoptera: Noctuidae) highly susceptible to Autographa californica multiple nucleopolyhedrovirus (AcMNPV) and M. separata NPV (MsNPV) - Xiang-Qian Meng; Gui-Ling Zheng; Chuan-De Zhao; Fang-Hao Wan; Chang-You Li (In Vitro Cellular & Developmental Biology - Animal, 2017)

Failure Mechanisms and Evolution Assessment of the Excavation Damaged Zones in a Large-Scale and Deeply Buried Underground Powerhouse - Hai-bo Li; Ming-chang Liu; Wan-bo Xing; Shuai Shao; Jia-wen Zhou (Rock Mechanics and Rock Engineering, 2017)

The function of OsbHLH068 is partially redundant with its homolog, AtbHLH112, in the regulation of the salt stress response but has opposite functions to control flowering in Arabidopsis - Hung-Chi Chen; Vicki Hsieh-Feng; Pei-Chun Liao; Wan-Hsing Cheng; Li-Yu Liu; Yun-Wei Yang; Ming-Hsin Lai; Men-Chi Chang (Plant Molecular Biology, 2017)

Evaluation of serum immunoglobulins concentrations and distributions in vitiligo patients - Yulong Li; Min Yang; Rui Zhang; Wan Liu; Kuo Zhang; Wei Wen; Lang Yi; Qiaoxian Wang; Mingju Hao; Hui Yang; Jianmin Chang; Jinming Li (Immunologic Research, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

A new cell line derived from embryonic tissues of Holotrichia parallela (Coleoptera:Scarabaeidae) - Miao-Miao Li; Gui-Ling Zheng; Rui Su; Fang-Hao Wan; Chang-You Li (In Vitro Cellular & Developmental Biology - Animal, 2016)

Risk assessment of maize drought disaster in southwest China using the Environmental Policy Integrated Climate model - Hui-cong Jia; Dong-hua Pan; Jing Li; Wan-chang Zhang; Rasul Ghulam (Journal of Mountain Science, 2016)

Streptomyces ferrugineus sp. nov., isolated from mangrove soil in Thailand - Chang-ying Ruan; Li Zhang; Wan-wan Ye; Xiu-chao Xie; Rattanaporn Srivibool; Kannika Duangmal; Wasu Pathom-aree; Zi-xin Deng; Kui Hong (Antonie van Leeuwenhoek, 2015)

Screening for Differentially Expressed Genes in Endophytic Fungus Strain 39 During Co-culture with Herbal Extract of its Host Dioscorea nipponica Makino - Chang-Hong Ding; Xiao-Wei Du; Ying Xu; Xiao-Meng Xu; Jin-Chao Mou; Dan Yu; Jun-Kai Wu; Fan-Jia Meng; Yan Liu; Wan-Li Wang; Li-Juan Wang (Current Microbiology, 2014)

Phenotypic characterization of C57BL/6J mice carrying the Disc1 gene from the 129S6/SvEv strain - Liang-Wen Juan; Chun-Chieh Liao; Wen-Sung Lai; Chia-Yuan Chang; Ju-Chun Pei; Wan-Rong Wong; Chih-Min Liu; Hai-Gwo Hwu; Li-Jen Lee (Brain Structure and Function, 2014)

EPO-Dependent Activation of PI3K/Akt/FoxO3a Signalling Mediates Neuroprotection in In Vitro and In Vivo Models of Parkinson’s Disease - Yu Jia; Shi-Jing Mo; Qi-Qi Feng; Ma-Li Zhan; Li-Si OuYang; Jia-Chang Chen; Yu-Xin Ma; Jia-Jia Wu; Wan-Long Lei (Journal of Molecular Neuroscience, 2014)

Molecular cloning and characterization of the mitogen-activated protein kinase kinase gene (MKK4) and its promoter sequence from oilseed rape (Brassica campestris L.) - Teng Guo Zhang; Qiong Qiong Chen; Ning Wang; Xiao Hui Xia; Juan Wang; Yan Chang; Ying Li Yang; Ning Yang; Wan Cang Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Better environmental data may reverse conclusions about niche‐ and dispersal‐based processes in community assembly - Li-Wan Chang; David Zelený; Ching-Feng Li; Shau-Ting Chiu; Chang-Fu Hsieh (Ecology, 2013)
Variation partitioning of species composition into components explained by environmental and spatial variables is often used to identify a signature of niche‐ and dispersal‐based processes in community assembly. Such interpretation, however, strongly depends on the quality of the environmental data available. In recent studies conducted in forest dynamics plots, the environment was represented only by readily available topographical variables. Using data from a subtropical broad‐leaved dynamics plot in Taiwan, we focus on the question of how would the conclusion about importance of niche‐ and dispersal‐based processes change if soil variables are also included in the analysis. To gain further insight, we introduced multiscale decomposition of a pure spatial component [c] in variation partitioning. Our results indicate that, if only topography is included, dispersal‐based processes prevail, while including soil variables reverses this conclusion in favor of niche‐based processes. Multiscale decomposition of [c] shows that if only topography was included, broad‐scaled spatial variation prevails in [c], indicating that other as yet unmeasured environmental variables can be important. However, after also including soil variables this pattern disappears, increasing importance of meso‐ and fine‐scaled spatial patterns indicative of dispersal processes.

Differential autophagic cell death under stress with ectopic cytoplasmic and mitochondrial-specific PPP2R2B in human neuroblastoma cells - Kang Fang; Hui-Fang Li; Chang-Heng Hsieh; Dan-Yu Li; Ding-Chieh Song; Wan-Ting Cheng; Zhi-Xuan Guo (Apoptosis, 2013)

The variation of tree beta diversity across a global network of forest plots - Miquel De Cáceres; Pierre Legendre; Renato Valencia; Min Cao; Li‐Wan Chang; George Chuyong; Richard Condit; Zhanqing Hao; Chang‐Fu Hsieh; Stephen Hubbell; David Kenfack; Keping Ma; et al. (Global Ecology and Biogeography, 2012)
Aims With the aim of understanding why some of the world's forests exhibit higher tree beta diversity values than others, we asked: (1) what is the contribution of environmentally related variation versus pure spatial and local stochastic variation to tree beta diversity assessed at the forest plot scale; (2) at what resolution are these beta‐diversity components more apparent; and (3) what determines the variation in tree beta diversity observed across regions/continents? Location World‐wide. Methods We compiled an unprecedented data set of 10 large‐scale stem‐mapping forest plots differing in latitude, tree species richness and topographic variability. We assessed the tree beta diversity found within each forest plot separately. The non‐directional variation in tree species composition among cells of the plot was our measure of beta diversity. We compared the beta diversity of each plot with the value expected under a null model. We also apportioned the beta diversity into four components: pure topographic, spatially structured topographic, pure spatial and unexplained. We used linear mixed models to interpret the variation of beta diversity values across the plots. Results Total tree beta diversity within a forest plot decreased with increasing cell size, and increased with tree species richness and the amount of topographic variability of the plot. The topography‐related component of beta diversity was correlated with the amount of topographic variability but was unrelated to its species richness. The unexplained variation was correlated with the beta diversity expected under the null model and with species richness. Main conclusions Because different components of beta diversity have different determinants, comparisons of tree beta diversity across regions should quantify not only overall variation in species composition but also its components. Global‐scale patterns in tree beta diversity are largely coupled with changes in gamma richness due to the relationship between the latter and the variation generated by local stochastic assembly processes.

Comparison of Bacterial and Fungal Communities Between Natural and Planted Pine Forests in Subtropical China - Ming Nie; Han Meng; Ke Li; Jia-Rong Wan; Zhe-Xue Quan; Chang-Ming Fang; Jia-Kuan Chen; Bo Li (Current Microbiology, 2012)

Use of Hydrologic and Hydrodynamic Modeling for Ecosystem Restoration - Jayantha Obeysekera; Laura Kuebler; Shabbir Ahmed; Miao-LI Chang; Vic Engel; Christian Langevin; Eric Swain; Yongshan Wan (Critical Reviews in Environmental Science and Technology, 2011)

Point patterns of tree distribution determined by habitat heterogeneity and dispersal limitation - Yi-Ching Lin; Li-Wan Chang; Kuoh-Cheng Yang; Hsiang-Hua Wang; I-Fang Sun (Oecologia, 2011)

Effects of PGI2 analogues on Th1- and Th2-related chemokines in monocytes via epigenetic regulation - Chang-Hung Kuo; Ying-Chin Ko; San-Nan Yang; Yu-Te Chu; Wei-Li Wang; Shau-Ku Huang; Huan-Nan Chen; Wan-Ju Wei; Yuh-Jyh Jong; Chih-Hsing Hung (Journal of Molecular Medicine, 2011)

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)